Transnational repression: data advances, comparisons, and challenges. Issue 1 (31st December 2022) - Dukalskis, Alexander; Furstenberg, Saipira; Gorokhovskaia, Yana; Heathershaw, John; Lemon, Edward; Schenkkan, Nate
ABSTRACT: Research on state repression generally focuses on what states do to populations within their own borders. However, recently scholars working at the intersection of comparative politics and international relations have begun to systematically analyse states repressing their populations outside their borders as part of their foreign policy. Variously called transnational repression, extraterritorial repression, or sometimes global authoritarianism, the focus is on the motives, methods, and effects of states extending repressive practices to their citizens abroad. Much of the research in this area has developed theories and findings using fieldwork and interview-based methods. Recently, however, multiple researchers and research groups have produced cross-national publicly available event data on transnational repression. This research note explains the main features of those datasets, including their scope, sources, structure, definitions, and strengths and limitations. In addition to descriptive introduction, it discusses the challenges associated with gathering data on transnational repression as well as suggestions for moving forward. The main aims are to introduce available data on transnational repression to researchers interested in working in this area and to highlight issues they may confront in gathering new data.